Dual Language Proficiency and the Educational Attainment of Latinos - Lutz, Amy (Migraciones Internacionales, 2017)
The relationship between Spanish maintenance and the educational attainment of English-speaking Latino students in the United States is investigated using data from the National Education Longitudinal Survey. The analysis indicates that biliterate students are significantly more likely to complete high school compared to their monolingual peers. Those with oral proficiency in Spanish and English are not significantly different in terms of their likelihood of high school completionthan were those who spoke only English. Biliterate students are also significantly more likely to enter college than those who speak only English. Overall, this research indicates that bilingualism, offers Latino students an advantage in terms of educational attainment. RESUMEN Usando datos de la Encuesta Logitudinal sobre Educación Nacional, se investiga la relación entre la conservación del español y los logros educativos de los estudiantes latinos en Estados Unidos que hablan inglés. El análisis indica que los estudiantes bilingües significativamente tienen más probabilidad de completar el bachillerato (high school) en comparación con sus compañeros monolingües. Aquellos estudiantes con la habilidad de hablar bien español e inglés no son significativamente diferentes –en términos de probabilidad– de terminar el bachillerato y tienen significativamente más probabilidad de entrar a la universidad que aquellos que solamente hablan inglés. En conclusión, esta investigación muestra que el bilingüismo ofrece a los estudiantes latinos una ventaja en términos de logros educativos.